2017
DOI: 10.1024/0301-1526/a000599
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between C-reactive protein and traditional risk factors in predicting mortality of older adults

Abstract: Summary:Background: Elevated levels of C-reactive protein (CRP) are known to be associated with cardiovascular (CV) morbidity and mortality in older adults, however, there seems to be heterogeneity of this association across subsets of individuals. We aim to assess the effects of interactions between CRP and one of the following traditional CV risk factors regarding allcause mortality in unselected elderly men and women: age, sex, body mass index, diabetes, and hypertension. Patients and methods: Three hundred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
3
0
1
Order By: Relevance
“…This association is corroborated by Thompson et al [45] who found that weight gain trajectories are associated with an elevated risk of inflammation. However, another study conducted in older adults showed that the interactions of CRP with obesity were not significant [46]. The inflammatory response is complex and involves numerous cytokines, soluble cytokine receptors, acute phase reactants, and other circulating factors.…”
Section: Discussionmentioning
confidence: 99%
“…This association is corroborated by Thompson et al [45] who found that weight gain trajectories are associated with an elevated risk of inflammation. However, another study conducted in older adults showed that the interactions of CRP with obesity were not significant [46]. The inflammatory response is complex and involves numerous cytokines, soluble cytokine receptors, acute phase reactants, and other circulating factors.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first cohort study to examine the combined effect of CRP and cognition on mortality among oldest-old aged 80 years or older in China. One prior study [13] among 6817 German unselected participants aged 65 years or older found significant interaction effects between age [HR CRP > 3.0 mg/L & ≥75 years: 3.18 (95% CI, 2.69, 3.75)], sex [HR CRP > 3.0 mg/L & male: 2.25 (95% CI, 1.92, 2.63)], and arterial hypertension [HR CRP > 3.0 mg/L & SBP ≥ 140 mmHg: 1.30 (1.10, 1.54)] with CRP (the cutoff value was 3.0 mg/L) on all-cause mortality. Our study extends the previous work by including a more comprehensive consideration of additional mortality risk factors such as a more accurate assessment of inflammation pathway biomarkers and study of a population of oldest-old of selected without consideration of function.…”
Section: Discussionmentioning
confidence: 99%
“…However, the high risk threshold value varies across different age groups. Though higher levels of CRP represent a risk factor for all-cause mortality in both middle-aged [11, 12], 65 -[13] and 75-year-old [14] cohorts, this association is attenuated in 80- and 85-year-old cohorts [15]. Furthermore, data about the epidemiology and predictive value of CRP, especially in oldest-old (aged ≥80 years), are sparse [15, 16]; the two previous studies of this age group were limited to less than 300 older persons each.…”
Section: Introductionmentioning
confidence: 99%
“…A adaptação do EDIP à população do ISA-capital, criando o EDIP-SP, gerou um padrão alimentar bastante coerente com a literatura vigente, no qual os grupos de alimentos "carnes processadas" tem carga positiva e os grupos "frutas, legumes e verduras" e "arroz e feijão" têm carga negativa, após ajuste por idade e sexoo ajuste se justifica porque esses são fatores associados à concentração de PCR em outros estudos (RUDOLF et al, 2017; e porque um estudo conduzido com a população do ISAcapital demonstrou variação importante no padrão alimentar entre sexos e faixas etárias (ANDRADE et al, 2016). O EDIP-SP foi inversamente associado ao IQD-R nas edições do estudo ISA-capital de 2008 e de 2015, reforçando seu potencial como indicador de qualidade da dieta, e sua associação com a concentração plasmática de PCR foi replicada na população masculina do ISA-capital 2015.…”
Section: Discussionunclassified